Job Hopping Karyawan Generasi Z Di Kota Semarang: Pengaruh Work Life Balance, Job Satisfaction, Dan Perceived Organizational Support - Anitaningsih, Rahayu; Nawatmi, Sri (Jurnal GeoEkonomi, 2026)
An examination of job mobility among Generation Z employees is oriented toward the influence of work–life equilibrium,occupational contentment, and perceived organizational backing. A quantitative framework was implemented through a survey design, utilizing a questionnaire administered to a sample of 100 Generation Z workers, from which 6 samples were excluded due to extreme outliers, yielding a final analyzed dataset of 94 valid respondents. Hypothesis verification was conducted using multiple linear regression analysis supported by SPSS 23. The findings reveal that work–life equilibrium and perceived organizational backing exert a positive effect on job mobility, whereas occupational contentment demonstrates no significant impact. This circumstance suggests that the inclination to pursue alternative employment intensifies when individuals attain balance between professional andpersonal domains and experience organizational support. Conversely, job satisfaction does not contribute to mobility decisions. In light of these outcomes, organizations are encouraged to enhance strategies related to work–life management and institutional support to mitigate turnover among Generation Z employees.